Regulated Agricultural Marketing System for Economic Development of Jajpur District in Orissa (India)- An Empirical Analysis (Global Journal of Management and Business Research, 2013)
Agriculture has played a key role in the process of socio-economic development of our country. Agriculture has all along been the most crucial sector of the Indian economy and even today agriculture and allied activities make the single largest attribution to Gross Domestic product accounting for nearly one fourth of the total. In Odisha, both Agriculture and Animal Husbandry provides employment directly or indirectly to around 65 per cent of the total workforce. It is ironic that Indian agriculture sector is moving in a reverse direction different from that of the non-agriculture sections. This tendency has been earmarked in the country throwing the responsibility to the agriculture market set ups failure to provide incentives to the former for more production and to stay on profession.
Keywords: regulated market committee(RMC); e-agriculture; agricultural knowledge based marketing systems (akms); orissa state agricultural marketing board(osam)